2019
DOI: 10.1007/s00280-019-03791-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug–drug interactions and nephrotoxicity in hematopoietic stem cell transplant adult recipients during bone marrow transplantation unit stay

Abstract: Purpose: Studies have documented potential drug-drug interactions (pDDI's) occurring in cancer patients mainly with solid malignancies, either in the ambulatory or hospital settings. While hematopoietic stem cell transplant (HSCT) patients during their bone marrow transplantation unit (BMTU) stay have rather complex medical regimens combining chemotherapy, anti-infectious agents, immunosuppressive agents and supportivecare drugs, studies on potential DDI's are lacking. Our objective was to evaluate the prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similar indications have been reported in other studies done in adult BMT units. 11,13,16,17 In their study, Visani et al 18 found moderate oral mucositis in 26%, gastroenteritis in 35%, and moderate vomiting and nausea in all patients who underwent autologous stem cell transplantation. Nephrotoxicity, cardiotoxicity, and interstitial or idiopathic pneumonia were not detected in any of their patients.…”
Section: Discussionmentioning
confidence: 95%
“…Similar indications have been reported in other studies done in adult BMT units. 11,13,16,17 In their study, Visani et al 18 found moderate oral mucositis in 26%, gastroenteritis in 35%, and moderate vomiting and nausea in all patients who underwent autologous stem cell transplantation. Nephrotoxicity, cardiotoxicity, and interstitial or idiopathic pneumonia were not detected in any of their patients.…”
Section: Discussionmentioning
confidence: 95%
“…Our study is consistent with the literature. Major drug groups causing DDIs were listed as immunosuppressants, antiepileptics and analgesics 9,39 . Gholaminezhad et al stated that antineoplastics such as busulfan and cyclophosphamide were common in drug–drug interactions in HSCT patients 40 …”
Section: Discussionmentioning
confidence: 99%
“…This is concerning because drugs metabolized by CYP3A4 are known to have potential interactions with other medications. Although the current study did not examine DDI, a previous study reported that DDIs in HSCT patients primarily resulted from pharmacokinetic mechanisms rather than pharmacodynamic interactions (1) .…”
Section: Therapeutic Pathwaymentioning
confidence: 91%
“…Patients with hematological malignancies, especially those undergoing hematopoietic stem cell transplantation (HSCT), face a high risk of pharmacotherapy-related problems due to complex drug regimens and patho-physiological variations affecting clearance organs. Potential drug-drug interactions (DDIs) are particularly common among HSCT patients in the bone marrow transplantation unit (1) . The identification and resolution of drug-related problems (DRP) constitute a very important role of the clinical pharmacist in managing drug therapy, and several general guidelines and recommendations have been provided to define the role of hospital pharmacists in caring for HSCT patients (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%